MONETARY MISGOVERNANCE AND INFLATION IN INDONESIA: REVISITING AL-MAQRĪZĪ THROUGH SIYASAH MĀLIYAH AND VECM EVIDENCE - Rusnaena R; Muhammad Majdy Amiruddin; Umaima U; Nur Isma Padila (Institut Agama Islam Negeri Bone, 2026)
This article examines inflation in Indonesia as a problem of monetary misgovernance through the lens of al Maqrīzī’s siyasah māliyah. While inflation is commonly analyzed through money supply, exchange rate movement, and institutional quality, this study argues that these variables also reflect deeper ethical questions concerning monetary authority, fiscal accountability, and distributive justice. Using a sequential explanatory mixed method design, the study first applies a Vector Error Correction Model to quarterly Indonesian data from 2000 to 2024. The model examines the long term relationship between inflation, broad money supply, real exchange rate movement, and the Corruption Perception Index, here abbreviated as CPerI to avoid confusion with the Consumer Price Index. The findings show that a 1 percent increase in broad money supply raises inflation by 0.28 percent within three quarters, a 1 percent real exchange rate depreciation increases inflation by 0.19 percent, and a one point decline in CPerI increases inflation by 0.12 percent within two quarters. These quantitative findings are then interpreted through textual analysis of al Maqrīzī’s Ighāthat al Umma and expert interviews. The integrated analysis shows that al Maqrīzī’s critique of excessive fulūs circulation, currency debasement, and corrupt fiscal extraction corresponds to contemporary problems of irresponsible liquidity expansion, currency instability, and weakened governance integrity. The article contributes to Islamic public finance by developing an ethical institutional model of inflation, in which price instability is understood not only as a macroeconomic outcome, but also as a failure of amanah, wilayat al mal, and distributive justice.